Salinity and sodicity in Pakistan's Punjab: A threat to sustainability of irrigated agriculture? - Kijne, Jacob W.; Kuper, M. (1995)
The development of groundwater for irrigation in Pakistan's Punjab has lowered water tables and markedly reduced the extent of waterlogged lands. However, the incidence of salinity has not been reduced at the same rate. This paper reviews IIMI's research studies in Pakistan, in which over the last five years soil and tubewell water samples have been collected at several research sites. Electrical conductivity of the saturated soil extract (ECe) and sodium absorption ratio (SAR) were found to be significantly higher in irrigated areas that have limited access to canal water of good quality. There are indications that farmers use irrigation water from tubewells to minimize the effects of salinity, e.g. by increasing the frequency of application when crops show signs of salt-induced water stress. Evidence is presented that farmers are not succeeding in the same way with respect to sodicity.